A facile approach to improve light induced cell sheet harvesting through nanostructure optimization. Issue 108 (20th October 2015) - Cheng, K.; Wan, H. P.; Weng, W. J.
Abstract : In the present study, the effects of nanostructure on the light-induced cell detachment property of anatase TiO2 films are investigated and discussed. Abstract : In the present study, the effects of nanostructure on the light-induced cell detachment property of anatase TiO2 films are investigated and discussed. Anatase dense films, nanodots films and porous films are prepared through sol–gel and phase separation-induced self-assembly based methods. It is found that all the films possessed good cell adhesion but there is a decrease in cell proliferation in the dense film. The porous film exhibits improved cell detachment performance in both single cell and cell sheet detachment tests. It only takes about 3 min of ultraviolet illumination for cell sheets to detach from the porous film, while those for nanodots film and dense film are 5 min and 10 min, respectively. The cell sheets harvested show good performance and thus can be further utilized in cell sheet tissue engineering. The beneficial effects of film nanostructure are ascribed to the differences of initial adsorption status of extracellular proteins, as well as their changes after ultraviolet illumination. The present work demonstrates that optimization of film nanostructures could be an effective approach to improve light induced cell sheet harvesting.